BRAND HERITAGE, CORPORATE REPUTATION AND BRAND IMAGE ON BUYING INTENTION - Guntur Pradipto Aji Raharjo (Universitas Dinamika, 2020)
This study aims to prove empirically how these three factors can influence purchasing decisions. This research model involves several variables of brand heritage, corporate reputation, purchase intention and brand image as additional variables. This research proves that brand heritage is still an important driver of customer purchase intentions or intentions. Similar results also occur in corporate reputation that supports this view that corporate reputation has a positive influence on buying intentions for Datsun products, and brand image that also influences consumers to buy Datsun products.